Review of Arctic sea-ice records over the last millennium from modern, historical, and proxy data sources - Natasha Leclerc; Jochen Halfar (Arctic, Antarctic, and Alpine Research)
Sea-ice loss and increasing unpredictability have disturbed and harmed Arctic peoples and ecosystems. In addition, studies demonstrate that sea ice plays a key role in climate variability and air–sea CO2 exchanges. Sea-ice data sets provide environmental baselines, validate proxies and models, and serve in regional and temporal comparisons. Accordingly, sea-ice and sea-ice–related variables are particularly valuable in climate modeling, paleoclimatology, and ecology to document past and present environmental changes and predict future outcomes. This article provides an overview of modern, historical, and long-term proxy sea-ice data sets that cover the last millennium. We describe available Arctic sea-ice data sources, discuss each data set’s strengths and limitations, and compare multisourced Arctic sea-ice histories in different regions. We conclude with remarks on the impacts of internal forcing from natural feedbacks and oscillations versus anthropogenic impacts on sea-ice variability. We draw upon remaining uncertainties regarding causes of past sea-ice variability and advocate for continued use of multiple data sources in sea-ice reconstruction–related studies and further development of a multisourced past sea-ice data network.